Morphological responses of a temperate intertidal foraminifer, Haynesina sp., to coastal acidification - Powers, Christopher; Paz, Alberto; Zyck, Amaelia; Harri, Kaylee; Geraci, Madison; Bernhard, Joan M.; Zhang, Ying (Frontiers in Microbiology, 2025)
Coastal acidification could have widespread impact on marine organisms, affecting the ability of calcifying organisms to build shells and skeletons through calcium carbonate precipitation. As an abundant group of calcifying organisms, some protists within the phylum Foraminifera demonstrate potential success under elevated partial pressure of carbon dioxide (pCO2) due to their ability to modulate intracellular pH. However, little is known about their responses under more extreme acidification conditions that are already seen in certain coastal environments. Here we exposed specimens of Haynesina sp., which belongs to a genus that is prevalent in temperate intertidal salt marshes, to moderate (pCO2 = 2386.05+/−97.14 μatm) and high acidification (pCO2 = 4797.64+/−157.82 μatm) conditions through the duration of 28 days. We demonstrate that although this species is capable of withstanding moderate levels of coastal acidification with little impact on overall test thickness, it can experience precipitation deficiency and even dissolution of the calcareous test under highly elevated pCO2. Interestingly, such a deficit was primarily seen among live foraminifera, as compared to dead specimens, throughout the four-week experiment. This study suggests that a combination of environmental stress and the physiological process of test formation (i.e., calcite precipitation) could induce thinning of the test surface. Therefore, with the acceleration of coastal acidification due to anthropogenic production of CO2, benthic foraminifera and other calcifying organisms among coastal ecosystems could reach a tipping point that leads to thinning and dissolution of their calcareous tests, which in turn, will impair their ecological function as a carbon sink.